THE SALMONELLAS A BACTERIOLOGICAL STUDY - ZOZAYA, JOSE; VARELA, GERARDO (My University, 1944)
Enteritis is prevalent in Mexico City and plays an important role in total mortality, mainly infantile This paper deals with the pathogenic role and bacteriologic identification of the Salmonella Cultures in enrichment media, biochemical reactions in
AN ESC NAC CIENC BIOL
Keywords: SALMONELLAS, BACTERIOLOGICAL, STUDY; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS